Optimization in Manual Aiming: Relating Inherent Variability and Target Size, and Its Influence on Tendency. Issue 4 (13th June 2022) - Roberts, James W.; Elliott, Digby; Burkitt, James J.
Abstract: For manual aiming, the optimized submovement model predicts a tendency toward target-center of primary movement endpoints (probabilistic strategy), while the minimization model predicts target undershooting ("play-it-safe" strategy). The spatial variability of primary movement endpoints directed toward a cross-hair (400–500 ms) (Session 1) were scaled by a multiplicative factor (x1 − 4) to form circular targets of different sizes (Session 2). In recognition of both models, it was predicted that the more that inherent variability exceeded the target size, the greater the tendency to shift from target-center aiming to target undershooting. The central tendency of primary movement endpoints was not influenced by the targets, while it neared target-center. These findings concur with a probabilistic strategy, although we speculate on factors that might otherwise foster a "play-it-safe" strategy.